ARGENTINE MILITARY ADVISERS IN HONDURAS - Balerini Casal, Emiliano (2018)
This article aims to analyze the influence the Argentine Army had in the Honduran Armed Forces to politically destabilize the government of the Sandinista National Liberation Front (FSLN), as well as desestabilize to the guerrillas of El Salvador and Guatemala, since 1980. It is necessary to briefly analyze the historical context that surrounded the Military Junta Argentina between 1976 and 1983, and the success that it had with its counterinsurgent policy. The extraterritorialization of its repressive system, proposed at the Conference of American Armies (CEA), in November 1979 in Bogotá, Colombia, is a point that must be analyzed. It is from this formal proposal of military advice to different countries inthe region that the intervention of the South American country in Central America occurred. It is intended to contribute to the studies and debates that in recent times are being conducted on this subject in different universities of Latin America, such as the UNAMin Mexico and the UBA in Argentina. The article represents an approach to the way in which the Argentine military dictatorship in Honduras operated, which served as a base for the training of La Contra.